Heston….Again?! Robust High‐Precision Option Pricing by Fourier Transforms: Contour Deformations and Double‐Exponential Quadrature. Issue 102 (26th July 2019) - Andersen, Leif B. G.; Lake, Mark
Abstract : Leif Andersen and Mark Lake discuss the background of their new paper "Robust High‐Precision Option Pricing by Fourier Transforms: Contour Deformations and Double‐Exponential Quadrature".